External cys/cySS redox state modification controls the intracellular redox state and neurodegeneration via Akt in aging and Alzheimer’s mouse model neurons - Ghosh, Debolina (J Alzheimers Dis, 2014)
The extracellular redox environment of cells is mainly set by the redox couple cysteine/cystine (cys/cySS) while intracellular redox is buffered by reduced/oxidized glutathione (GSH/GSSG), but controlled by NAD(P)H/NAD(P). With aging, the extracellular redox environment shifts in the oxidized direction beyond middle-age. Since aging is the primary risk factor in Alzheimer’s disease (AD), here our aim was to determine if a reduced extracellular cys/cySS redox potential of cultured primary mouse neurons changes the intracellular redox environment, affects pAkt levels and protects against neuron loss. A reductive shift in cys/cySS in the extracellular medium of neuron cultures from young (4 month) and old (21 month) neurons from non-Tg (non-transgenic) and triple transgenic AD-like mice (3xTg-AD), caused an increase in intracellular NAD(P)H and GSH levels along with lower ROS levels. Importantly, the imposed reductive shift decreased neuron death markedly in the 21 month neurons of both genotypes. Moreover, a reduced cys/cySS redox state increased the pAkt/Akt ratio in 21 month aging and AD-like neurons that positively correlated with a decreased neuron loss. Our findings demonstrate that manipulating the extracellular redox environment toward a more reduced redox potential is neuroprotective in both aging and AD-like neurons and may be a powerful and pragmatic therapeutic tool in aging and age-related diseases like AD.